2015
DOI: 10.1007/s13346-015-0251-1
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing of insulin microneedles for transdermal delivery

Abstract: Inkjet printing technology was used to apply insulin polymeric layers on metal microneedles for transdermal delivery. A range of various polymers such as gelatin (GLN), polyvinyl caprolactame-polyvinyl acetate-polyethylene glycol (SOL), poly(2-ethyl-2-oxazoline) (POX) and trehalose (THL) were assessed for their capacity to form thin uniform and homogeneous layers that preserve insulin intact. Atomic force microscopy (AFM) showed homogeneous insulin-polymer layers without any phase separation while SOL demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…Inkjet printing was then employed to apply coatings of insulin and sugar alcohol solutions through a piezoelectric dispenser. This 2D printing approach has been previously used for coating of metal MNs (Ross et al, 2015;Uddin et al, 2015) where by optimizing the applied voltage (mV) and the pulse duration (ms) droplets of 300 pL volume with consistent particle size of 100 -110 m as observed by the printer's stroboscope, were produced. The dispenser's tip (50m) was kept close to the microneedle surface to avoid losses of the coating material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inkjet printing was then employed to apply coatings of insulin and sugar alcohol solutions through a piezoelectric dispenser. This 2D printing approach has been previously used for coating of metal MNs (Ross et al, 2015;Uddin et al, 2015) where by optimizing the applied voltage (mV) and the pulse duration (ms) droplets of 300 pL volume with consistent particle size of 100 -110 m as observed by the printer's stroboscope, were produced. The dispenser's tip (50m) was kept close to the microneedle surface to avoid losses of the coating material.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, to determine the effect of needle shape on the force required for skin penetration, piercing tests using porcine skin were conducted. In order to have a frame of reference with respective literature, metallic MN arrays were tested as well, the fabrication and physical characteristics of which, are described elsewhere (Ross et al, 2015). A texture analyser was employed, and the MN array was mounted on the moving probe using double-sided adhesive tape.…”
Section: Penetration Of Mn In Porcine Skinmentioning
confidence: 99%
“…Most commonly, aqueous coating solutions are used to create a uniform thin film of material on a metallic MN surface [4,7,[13][14][15]. Whilst these studies have demonstrated the ability to coat hydrophilic drugs and particulates onto MNs, published reports of successful MN coating using hydrophobic materials are limited and typically describe low drug loading doses [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[86] Currently, such technique has been main utilized to coat pre-fabricated microneedles with drugs for the personalized and combined drug loading. [87,88] Photopolymerization-based technique refers to the fabrication of 3D models by selectively polymerization of photo-sensitive polymers under the laser/light irradiation. Such technique could fabricate polymeric microneedles by consistent layer-by-layer polymerization of UV-sensitive polymers through the photopolymerization curing process.…”
Section: Methods For the Fabrication Of Polymeric Microneedlesmentioning
confidence: 99%